2006
DOI: 10.1111/j.1365-2133.2005.07114.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Malassezia species in pityriasis versicolor and seborrhoeic dermatitis in Greece. Typing of the major pityriasis versicolor isolate M. globosa

Abstract: Malassezia species isolation rates were in agreement with those reported from South-west Europe. PCR-SSCP of the ITS 1 is useful for highlighting prospective clinical implications of M. globosa subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
3
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 32 publications
(39 reference statements)
4
69
3
4
Order By: Relevance
“…62 Gupta and Gaitanis reported a greater amount of M. globosa. 63,64 Tajima was the only author to report M. restricta as being the most common. 65 Nakabayashi and Sei found that children with SD had a greater amount of Malassezia (M. furfur and M. globosa) compared to children without the disease.…”
Section: Malassezia Sppmentioning
confidence: 99%
“…62 Gupta and Gaitanis reported a greater amount of M. globosa. 63,64 Tajima was the only author to report M. restricta as being the most common. 65 Nakabayashi and Sei found that children with SD had a greater amount of Malassezia (M. furfur and M. globosa) compared to children without the disease.…”
Section: Malassezia Sppmentioning
confidence: 99%
“…To overcome the limits of morphological assessment, recent studies have used a variety of molecular methods such as the nested polymerase chain reaction (PCR) 12 , real-time PCR 13 , pulsed field gel electrophoresis (PFGE) 14 , amplified fragment length polymorphism (AFLP) 15,16 , denaturing gradient gel electrophoresis (DGGE) 16 , random amplification of polymorphic DNA (RAPD) 16,17 , single strand conformation polymorphism (SSCP) 18 , terminal fragment length polymorphism (tFLP) 19 , restriction fragment length polymorphism (RFLP) [20][21][22][23] , and sequencing analysis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Variable M. furfur subtypes (Figure 1: strains GS4A/GS4B and GS9A/GS9B) from different anatomical regions showed different M13 fingerprints. As multiple Malassezia species are isolated from individuals (Gaitanis et al, 2006b;Tajima et al, 2008), an analogous intra-species polymorphism is expected.…”
mentioning
confidence: 99%